Plant virology in Africa [1] - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Plant virology in AfricaProfessor Roger Hull, of Norwich, England, writes in support of the Viewpoint article by Dr M Tresh published in Spore 76 entitled The future of plant virology in Africa. 'I strongly support the need for the enhancement of...